Elaboração de pó liofilizado da polpa de noni (Morinda citrifolia) e determinação de compostos bioativos em diversos componentes da fruta e no pó liofilizad - Fontes, Rafaela Figueiredo (2018)
Morinda citrifolia, popularly known as noni, is native from Southeast Asia. In Brazil, its recent introduction began gradually, through people who brought seeds, probably from the Caribbean or Polynesia. The improvements in health, increased the consumption of this fruit among Brazilians. The northeast region has an appreciable planting of the Morinda citrifolia, mainly in the regions located between the states of Sergipe and Ceará. However, the National Health Surveillance Agency (ANVISA) states that the pharmacological and therapeutic effects of the fruit have not yet been fully explained. The objective of the present work was to elaborate lyophilized powder of noni pulp (Morinda citrifolia) and to determine bioactive compounds in several components of the fruit and of lyophilized powder. The fruits were purchased in the municipal market of the city of Aracaju-SE. These were selected according to their degree of ripening (mature) and dismembered in seed, peel and pulp. Part of which was processed in lyophilizer for 48h period, temperature of -54.9ºC, pressure 6,11 mbar and vacuum of 0,42 mbar. The fruit was characterized for its centesimal composition, and its lyophilized extract had the best activity, in acetone, for the FRAP antioxidant method, as well as for the ABTS ++ radical. For phenolics, the lyophilized powder (7486.37 μg EAG/g) obtained better performance in aqueous medium, pulp (464.44 μg EAG/g) in ethanolic extract, seed and peel in acetone with values of 2329.99 μg EAG/g and 313.29 μg EAG/g, respectively. Among the noni constituents, flavonoids (156.94 μg querc./g sample) showed a better response in the acetone seed extract. For the other extracts, lyophilized powder showed more expressive results. The analysis of the chromatographic profiles for flavonoids and their identification was possible through HPLC/DAD, and bioactive compounds such as rutin, kaempferol and artepillin C were identified. Ascorbic acid was quantified in a higher concentration (336.62 mg / 100g) in the lyophilized powder of the fruit. The sugar contents were higher in the lyophilized pulp powder, sucrose (4.69g / 100g), fructose (6.37g / 100g), glucose (9.20g / 100g). Thus being the higher potential of antioxidant effect of the various components of the fruit was established, as well as the greater conservation of this potential through the application of lyophilization.